If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(-8k-3)-2=-(-7k-5)
We simplify the equation to the form, which is simple to understand
-(-8k-3)-2=-(-7k-5)
Remove unnecessary parentheses
+8k+3-2=-(-7k-5)
Remove unnecessary parentheses
+8k+3-2=+7k+5
We move all terms containing k to the left and all other terms to the right.
+8k-7k=+5-3+2
We simplify left and right side of the equation.
+1k=+4
We divide both sides of the equation by 1 to get k.
k=4
| 7x+16-6x=-3-10 | | 3v-8=28 | | 2655*100=x*45 | | A+bi=-15+6i | | 2x^2+x+5= | | 4X+5X-3=6 | | 36=-9(y+1) | | 2.25-4.7= | | 8x+7=-12 | | 6(7-f)+f=36f | | (x-150)+x=430 | | 7(z-3)= | | 4x^3+12x^2-49x-147=0 | | -5(2y-2)-y=-3(y-5) | | -1.5(-1.5)= | | 6(4a+12)=8(3s-14) | | (6x-6)=24 | | 2e^4x-2=2 | | 16-7y+14=3y+14-7 | | F-8=6+3f | | 2+r=2-7r | | 9.2+3.1=2.06+1.15x | | -7-7(-5n-5)=4(5n-7)-4 | | 49y=12(4y+12) | | w+-8=6 | | (2y+2)-(y+6)= | | 0=16t^2-300t+1000 | | 8(e-5)=2(3e-8) | | -1.5(-4.7)-4.7= | | 19-3n=-29 | | 14-x=-10 | | 3a+8=y |